1987 Agricultural Research, Southeast Kansas Branch Station - L. W. Lomas; K. W. Kelley; J. L. Moyer; D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 1987)
Research on beef cattle and crops at Southeast Kansas Branch Station.
Keywords: beef cattle; forage; wheat; soybeans; weeds; grain sorghum